2019
DOI: 10.1093/nar/gkz1185
|View full text |Cite
|
Sign up to set email alerts
|

Adapted formaldehyde gradient cross-linking protocol implicates human eIF3d and eIF3c, k and l subunits in the 43S and 48S pre-initiation complex assembly, respectively

Abstract: One of the key roles of the 12-subunit eukaryotic translation initiation factor 3 (eIF3) is to promote the formation of the 43S and 48S pre-initiation complexes (PICs). However, particular contributions of its individual subunits to these two critical initiation reactions remained obscure. Here, we adapted formaldehyde gradient cross-linking protocol to translation studies and investigated the efficiency of the 43S and 48S PIC assembly in knockdowns of individual subunits of human eIF3 known to produce various… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 57 publications
4
32
0
Order By: Relevance
“…In addition, weak but reproducible binding between eIF3d and eIF3a and eIF3c subunits was also detected, in contrast to other eIF3 subunits ( Figures S5 D and S5E). Because human eIF3d was shown to interact with the mRNA cap ( Lee et al., 2016 ) and together with several other eIF3 subunits (including eIF3a, c, e, k, and l) was proposed to promote recruitment of selected mRNAs to the 43S PIC to control their expression in response to various stresses and cellular signals ( Herrmannová et al., 2020 ; Lee et al., 2015 ; Shah et al., 2016 ), we speculate that these contacts play a pivotal role in coordinating the eIF3d-specific functions with the rest of eIF3 on the ribosome.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, weak but reproducible binding between eIF3d and eIF3a and eIF3c subunits was also detected, in contrast to other eIF3 subunits ( Figures S5 D and S5E). Because human eIF3d was shown to interact with the mRNA cap ( Lee et al., 2016 ) and together with several other eIF3 subunits (including eIF3a, c, e, k, and l) was proposed to promote recruitment of selected mRNAs to the 43S PIC to control their expression in response to various stresses and cellular signals ( Herrmannová et al., 2020 ; Lee et al., 2015 ; Shah et al., 2016 ), we speculate that these contacts play a pivotal role in coordinating the eIF3d-specific functions with the rest of eIF3 on the ribosome.…”
Section: Resultsmentioning
confidence: 99%
“…Among its initiation roles, eIF3 critically contributes to the assembly of the 43S PIC through a multitude of contacts that it makes with other eIFs, ensuring their recruitment to the 40S ( Asano et al., 2001a ; Valášek et al., 2017 ). Mammalian eIF3 comprises 12 subunits (eIF3a–m; excluding j), of which 8 form the PCI (proteasome/CSN/eIF3)/MPN (Mpr1/Pad1 N-terminal) octameric structural core (eIF3a, c, e, f, h, k, l, and m) ( des Georges et al., 2015 ; Herrmannová et al., 2020 ; Sun et al., 2011 ; Wagner et al., 2014 , 2016 ). Interestingly, unlike their mammalian hosts, kinetoplastids do not encode the eIF3m subunit ( Li et al., 2017 ; Meleppattu et al., 2015 ; Rezende et al., 2014 ) co-forming the octameric core in all known “12-subunit” species, strongly suggesting that the structure of their eIF3 core differs from that of mammals.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing formaldehyde concentration progressively preserved BC200 interactions; however, cross-linking with greater than 2% formaldehyde rendered cell lysis inefficient (data not shown). Although 2% formaldehyde is considerably higher than has been used in previous studies, this approach was necessary to maximally preserve BC200 complexes ( 52 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
“…Another subunit of eIF3, eIF3l, was also shown to have cap-binding activity ( Kumar et al, 2016 ). Since eIF3l and eIF3k are not required for cell growth and 48S complex formation in vitro ( Smith et al, 2013 ; Wagner et al, 2016 ) and were recently shown to inhibit mRNA recruitment to the 43S pre-initiation complex ( Herrmannová et al, 2019 ), the function of eIF3l’s cap-binding activity is currently unknown.…”
Section: New Non-canonical Mechanisms Of Translation Initiation Involmentioning
confidence: 99%